A Canadian Bankclerk - Preston, Jack, 1888- (Book collections on Project MUSE., 1973)
Of this novel of Canadian business life and village and city social conditions in the early twentieth century, the author explains that his object is 'to enlighten the public concerning life behind the wicket and thus pave the way for the legitimate organization of bankclerks into a fraternal association.'